Study on the factors affecting on phosphate removal by alum - Trần Văn, Quy; Nguyễn, Hà Thị; Nguyễn, Đồng Thành; Nguyễn, Hoàng Viết (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 1SDO - 10.25073/2588-1094/vnuees.4212, 2017)
A bstract: The impact of pH, reaction time, Al 3+ / P molar ratio, phosphate concentration and polymer concentration on the phosphate removal by alum sunfate was carried out. The obtained results showed that optimal conditions for phosphate removal by Al 2 (SO 4 ) 3 .18H 2 O was as follow: pH of 6,0; reaction time about 30 minutes, Al 3+ /P mole ratio of 2:1; polymer concentration of 1,0 mg/L. Initial phosphate concentration did not affect significantly on the removal efficiency. Test with real wastewater (taken from To Lich river) proved that these abover condition was applicable.